Rational and Behavioral Decision Making in the Indian IPO Market - Jain, Neeta; Agarwal, Nupur (Indian Journal of Research in Capital Markets, 2014)
The underpricing of IPOs has been an extensively researched topic across countries and time. There have been various approaches in academic research to tackle the issue of underpricing and overpricing of IPOs. The IPO issue process is a long process and it disseminates plenty of information until it gets listed on a stock exchange. The present study classified this information in three categories as information available in the offer documents of the IPO issuing firm, information of the performance of past IPOs, and information of the subscription pattern during subscription period of an IPO. This paper is an empirical study which aimed to use the above mentioned three types of information to find out the determinants of initial returns of IPOs in India.